Performance, Emissions and Combustion Characteristics of a Single Cylinder Diesel Engine Fuelled with Blends of Jatropha Methyl Ester and Diesel - Debasish Padhee; Hifjur Raheman (Center of Biomass & Renewable Energy (CBIORE), 2014)
In order to meet the energy requirements, there has been growing interest in alternative fuels like biodiesels, ethyl alcohol, biogas, hydrogen and producer gas to provide a suitable diesel substitute for internal combustion engines. An experimental investigation was performed to study the performance, emissions and combustion characteristics of diesel engine fuelled with blends of Jatropha methyl ester and diesel. In the present work three different fuel blends of Jatropha methyl ester (B10, B20, B40 and B100) were used. The increments in load on the engine increase the brake thermal efficiency, exhaust gas temperature and lowered the brake specific fuel consumption. The biodiesel blends produce lower carbon monoxide & unburned hydrocarbon emission and higher carbon dioxide & oxides of nitrogen than neat diesel fuel. From the results it was observed that the ignition delays decreased with increase in concentration of biodiesel in biodiesel blends with diesel. The combustion characteristics of single-fuel for biodiesel and diesel have similar combustion pressure and HRR patterns at different engine loads but it was observed that the peak cylinder pressure and heat release rate were lower for biodiesel blends compared to those of diesel fuel combustion.